Stress-strain Behaviour of Teak (Tectona grandis) under Repeated Loading in Compression - Jain, V. K. (Indian Forester, 1992)
Wood possesses both elastic and plastic propertirs. Highly crystalline regions in an isolated state would have elastic properties. Amorphous lignin would have plastic properties. But there are no isolated elements in wood-tissue. In wood, elastic and plastic regions are interwined and are attributable to different anaromical elements and chemical constituents of the cell-wall. The results have indicated the presence of plastic part of the strain even at very low applied loads, viz. 5% of the elastic limit load. It stays constant upto 30%, increases at 40% and then again stays constant upto 90% of the load required at elastic limit. It was further shown that the elastic-plastic material like wood starts behaving as an elastic one on repeated loadingdeIoading cycles, within the elastic limit.